CeO2 / Zn0. 5Cd0. 5S composite photocatalyst with 2D / 0D structure as well as preparation method and application of CeO2 / Zn0. 5Cd0. 5S composite photocatalyst
By uniformly distributing Zn0.5Cd0.5S nanoparticles on the surface of CeO2 nanosheets and forming CeO2/Zn0.5Cd0.5S heterojunction, the problems of easy agglomeration and low photocatalytic efficiency of Zn0.5Cd0.5S photocatalysts are solved, and high efficiency is achieved Photocatalytic activity and photohydrogen production activity.
Patent Information
- Application Number
- CN202411516076.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-02-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The isolated Zn0.5Cd0.5S photocatalyst has the disadvantages of fast photogenerated electron-hole pair recombination rate, easy agglomeration and photocorrosion, which limits its photocatalytic efficiency and practical application.
By preparing CeO2/Zn0.5Cd0.5S composite photocatalyst with 2D/OD structure, the 0D Zn0.5Cd0.5S nanoparticles are uniformly distributed on the surface of 2D CeO2 nanosheets to form a CeO2/Zn0.5Cd0.5S heterojunction to promote photogenesis Separation and migration of carriers.
It improves photocatalytic activity, enhances the activity of photolysis of hydrogen production, has good application prospects and industrialization potential, and provides a safe and reliable, simple operation and low-cost preparation method.
Smart Images

Figure CN119386895A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photocatalytic materials, and in particular to a CeO2 / Zn photocatalytic material having a 2D / 0D structure. 0.5 Cd 0.5 S composite photocatalyst and its preparation method and application. Background Art
[0002] In recent years, with the rapid development of industrialization and urbanization, the increasingly serious energy shortage and environmental pollution problems have aroused widespread public concern. In order to solve these problems, researchers have developed a photocatalytic technology that has the advantages of high efficiency, environmental protection and renewability, and is considered to be one of the effective ways to solve energy shortage and environmental problems. Photocatalytic technology, due to its excellent semiconductor optical properties, can convert sunlight into chemical energy and is considered to be one of the sustainable and attractive strategies to solve human crises.
[0003] In order to improve the efficiency of solar energy utilization, in the field of photocatalysis, there is an urgent need to design and synthesize efficient and stable visible light responsive photocatalysts. x Cd 1-x S ternary solid solution, with excellent visible light absorption performance and adjustable band gap. x Cd 1-x In the S family, Zn 0.5 Cd 0.5 Due to its suitable band gap, strong visible light absorption performance and high conduction band potential (with optimal photocatalytic activity), S has potential application value in photodegradation of pollutants, water decomposition to produce hydrogen and carbon dioxide photoreduction.
[0004] However, isolated Zn 0.5 Cd 0.5 S photocatalysts have disadvantages such as high recombination rate of photogenerated electron-hole pairs, easy agglomeration and photocorrosion, which greatly limit their photocatalytic efficiency and practical application. 0.5 Cd 0.5 The photocatalytic performance of S was 0D Zn 0.5 Cd 0.5 Combining S with other semiconductors has become one of the most attractive approaches.
[0005] In the prior art, many semiconductor materials (such as Cu2S, WO3, Sn3O4 and g-C3N4) are used to react with Zn 0.5 Cd 0.5S composite to improve photocatalytic performance. As a typical n-type semiconductor, cerium dioxide (CeO2) has attracted widespread attention in the field of photocatalysis due to its low price, high chemical stability and environmental friendliness. At the same time, 2D CeO2 has a high specific area and is widely used as a photocatalyst for hydrogen production and removal of pollutants in water. However, the photocatalytic efficiency of single-component CeO2 is severely limited by the narrow visible light absorption range (band gap of 2.8eV) and the rapid recombination of photogenerated carriers. Therefore, researchers designed and constructed a series of CeO2-based heterojunctions, such as Ag2O / CeO2, ZnIn2S4 / CeO2 and CdSe / CeO2. Compared with single components, these heterojunctions exhibit stronger photocatalytic performance. The formation of composite materials can effectively promote the separation and transfer of photogenerated charges, thereby improving the photocatalytic efficiency. However, the photocatalytic efficiency of CeO2 / Zn 0.5 Cd 0.5 There are very few reports on the preparation and photocatalytic activity of S composites, and there is a lack of a systematic preparation method to achieve the above-mentioned photocatalytic performance. Summary of the invention
[0006] The object of the present invention is to provide a CeO2 / Zn with a 2D / 0D structure. 0.5 Cd 0.5 S composite photocatalyst and preparation method and application thereof, simple operation, low cost, 0D Zn 0.5 Cd 0.5 S nanoparticles are evenly distributed on the surface of 2D CeO2 nanosheets. 0.5 Cd 0.5 CeO2 / Zn is formed between S and CeO2 0.5 Cd 0.5 S heterojunction will greatly promote the separation and migration of photogenerated carriers.
[0007] To achieve the above object, the present invention provides a CeO2 / Zn2O3 / Zn2O3 / Zn2O3 having a 2D / 0D structure. 0.5 Cd 0.5 The preparation method of S composite photocatalyst comprises the following steps:
[0008] S1, preparing CeO2 nanosheets;
[0009] S2, preparing CeO2 nanosheet suspension;
[0010] S3, preparing a mixed solution of cadmium acetate and zinc acetate;
[0011] S4, preparing sodium sulfide solution;
[0012] S5, according to a certain ratio, the mixed solution of cadmium acetate and zinc acetate obtained in S3 is dripped into the CeO2 nanosheet suspension obtained in S2 for stirring, and then the sodium sulfide solution obtained in S4 is slowly dripped into and stirred after ultrasonic treatment, and the CeO2 / Zn nanosheet suspension is obtained after centrifugation, washing and freeze drying. 0.5 Cd 0.5 S composite photocatalyst.
[0013] Preferably, S1 comprises the following steps:
[0014] S11, dissolving cerium nitrate hexahydrate and ammonium bicarbonate in deionized water respectively to obtain a cerium nitrate hexahydrate solution and an ammonium bicarbonate solution;
[0015] S12. Add the cerium nitrate hexahydrate solution obtained in S11 to the ammonium bicarbonate solution obtained in S11, perform magnetic stirring, then let stand, centrifuge, and wash, collect the washed product, dry it, and then calcine it to obtain CeO2 nanosheets.
[0016] Preferably, in S11, the molar ratio of cerium nitrate hexahydrate in the cerium nitrate hexahydrate solution to ammonium bicarbonate in the ammonium bicarbonate solution is 1:1-4.
[0017] Preferably, in S12, the standing temperature is 293-313 K and the time is 12-36 h, the drying temperature is 70-110° C. and the time is 8-15 h, and the calcination temperature is 673-873 K and the time is 2-8 h.
[0018] Preferably, S2 is specifically:
[0019] The CeO2 nanosheets obtained in S1 were added into deionized water, followed by ultrasonic dispersion treatment to obtain a CeO2 nanosheet suspension.
[0020] Preferably, in S3, the mixed solution of cadmium acetate and zinc acetate is cadmium acetate dihydrate: zinc acetate dihydrate: deionized water = 3mmol:3mmol:40ml.
[0021] Preferably, in S4, the sodium sulfide solution is sodium sulfide nonahydrate: deionized water = 3 mmol: 20 ml.
[0022] Preferably, in S5, the stirring time of the stirring treatment is 0.5 to 1.5 h; the ultrasonic time of the post-ultrasonic stirring treatment is 20 to 40 min, and the stirring time is 8 to 24 h.
[0023] To achieve the above object, the present invention also provides a CeO2 / Zn with a 2D / 0D structure. 0.5 Cd 0.5 S composite photocatalyst, the CeO2 / Zn0.5 Cd 0.5 CeO2 and Zn in S composite photocatalyst 0.5 Cd 0.5 The mass ratio of S is 5-20:80-95.
[0024] To achieve the above object, the present invention also provides a CeO2 / Zn with a 2D / 0D structure. 0.5 Cd 0.5 Application of S composite photocatalyst in photocatalytic water decomposition to produce hydrogen.
[0025] Therefore, the present invention adopts the above-mentioned CeO2 / Zn with 2D / 0D structure. 0.5 Cd 0.5 S composite photocatalyst and preparation method and application, the beneficial effects are as follows:
[0026] (1) CeO2 / Zn prepared by the present invention 0.5 Cd 0.5 S composite photocatalyst, its Zn 0.5 Cd 0.5 S nanoparticles are evenly dispersed on the surface of CeO2 nanosheets, reducing Zn 0.5 Cd 0.5 S agglomeration increases the specific surface area of the catalyst and improves the photocatalytic activity; in addition, 0.5 Cd 0.5 CeO2 / Zn 0.5 Cd 0.5 S heterojunction will accelerate the separation and migration of photogenerated charges and further improve the photocatalytic activity.
[0027] (2) CeO2 / Zn prepared by the present invention 0.5 Cd 0.5 The S composite photocatalyst has high activity for photocatalytic hydrogen production from water and has good application and industrialization prospects in the fields of energy and environment.
[0028] (3) The preparation method provided by the present invention is safe and reliable, easy to operate, low-cost, and suitable for industrial production.
[0029] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The present invention is a CeO2 / Zn with 2D / 0D structure 0.5 Cd 0.5 X-ray diffraction pattern of S composite photocatalyst embodiment;
[0031] Figure 2The present invention is a CeO2 / Zn with 2D / 0D structure 0.5 Cd 0.5 Scanning electron microscope images of the S composite photocatalyst embodiment, where (a) is pure CeO2 photocatalyst, (b) is pure Zn 0.5 Cd 0.5 S photocatalyst, (c) CeO2 / Zn at 1 μm 0.5 Cd 0.5 S composite photocatalyst, (d) CeO2 / Zn at 500 nm 0.5 Cd 0.5 S composite photocatalyst;
[0032] Figure 3 The present invention is a CeO2 / Zn with 2D / 0D structure 0.5 Cd 0.5 Energy dispersion spectrum of the S composite photocatalyst embodiment, where (a) is CeO2 / Zn 0.5 Cd 0.5 S composite photocatalyst morphology, (b) is the Ce element distribution diagram, (c) is the O element distribution diagram, (d) is the Zn element distribution diagram, (e) is the Cd element distribution diagram, and (f) is the S element distribution diagram;
[0033] Figure 4 The present invention is a CeO2 / Zn with 2D / 0D structure 0.5 Cd 0.5 Electron microscopy images of an embodiment of the S composite photocatalyst, wherein (a) is a transmission electron microscopy image and (b) is a high-resolution transmission electron microscopy image;
[0034] Figure 5 The present invention is a CeO2 / Zn with 2D / 0D structure 0.5 Cd 0.5 Comparison diagram of hydrogen production from water by photolysis using an application example of the S composite photocatalyst, wherein (a) is a comparison diagram of hydrogen production amount; and (b) is a comparison diagram of hydrogen production rate. DETAILED DESCRIPTION
[0035] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.
[0036] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.
[0037] Embodiment 1
[0038] A CeO2 / Zn 0.5 Cd 0.5 The preparation method of S composite photocatalyst comprises the following steps:
[0039] S1. Preparation of CeO2 nanosheets:
[0040] S11. Dissolve 2.78 g of cerium nitrate hexahydrate and 1.50 g of ammonium bicarbonate in 100 ml of deionized water by stirring.
[0041] S12, the two solutions prepared in S11 were quickly mixed and continuously magnetically stirred for 30 minutes, and allowed to stand at 303 K for 24 hours. Centrifuged, washed, and dried at 353 K for 12 hours. Calcinated at 773 K for 4 hours to obtain CeO2 nanosheets.
[0042] S2. Preparation of CeO2 nanosheet suspension: Add 0.038 g of CeO2 nanosheet obtained in step S12 into 50 ml of deionized water and disperse by ultrasonic for 30 min.
[0043] S3. Prepare a mixed solution of cadmium acetate and zinc acetate: add 3 mmol of cadmium acetate dihydrate and 3 mmol of zinc acetate dihydrate into 40 ml of deionized water, stir to completely dissolve them, and obtain a homogeneous solution of cadmium acetate and zinc acetate.
[0044] S4. Prepare a sodium sulfide solution: add 6 mmol of sodium sulfide nonahydrate to 40 ml of deionized water, stir to completely dissolve it, and obtain a sodium sulfide solution.
[0045] S5, drip the mixed solution of cadmium acetate and zinc acetate obtained in S3 into the CeO2 nanosheet suspension obtained in S2 and stir for 1 hour, then slowly drip the sodium sulfide solution obtained in S4 and ultrasonicate for 30 minutes, then stir for 12 hours, the reaction product is centrifuged and washed with deionized water and ethanol, and freeze-dried to obtain 5% CeO2 / Zn 0.5 Cd 0.5 S composite photocatalyst.
[0046] Embodiment 2
[0047] A CeO2 / Zn 0.5 Cd 0.5 The preparation method of S composite photocatalyst comprises the following steps:
[0048] S1. Preparation of CeO2 nanosheets:
[0049] S11. Dissolve 2.78 g of cerium nitrate hexahydrate and 1.50 g of ammonium bicarbonate in 100 ml of deionized water by stirring.
[0050] S12, the two solutions prepared in S11 were quickly mixed and continuously magnetically stirred for 30 minutes, and allowed to stand at 303 K for 24 hours. Centrifuged, washed, and dried at 353 K for 12 hours. Calcinated at 773 K for 4 hours to obtain CeO2 nanosheets.
[0051] S2. Preparation of CeO2 nanosheet suspension: Add 0.081 g of CeO2 nanosheet obtained in step S12 into 50 ml of deionized water and disperse by ultrasonic for 30 min.
[0052] S3. Prepare a mixed solution of cadmium acetate and zinc acetate: add 3 mmol of cadmium acetate dihydrate and 3 mmol of zinc acetate dihydrate into 40 ml of deionized water, stir to completely dissolve them, and obtain a homogeneous solution of cadmium acetate and zinc acetate.
[0053] S4. Prepare a sodium sulfide solution: add 6 mmol of sodium sulfide nonahydrate to 40 ml of deionized water, stir to completely dissolve it, and obtain a sodium sulfide solution.
[0054] S5, drip the mixed solution of cadmium acetate and zinc acetate obtained in S3 into the CeO2 nanosheet suspension obtained in S2 and stir for 1 hour, then slowly drip the sodium sulfide solution obtained in S4 and ultrasonicate for 30 minutes, then stir for 12 hours, the reaction product is centrifuged and washed with deionized water and ethanol, and freeze-dried to obtain 10% CeO2 / Zn 0.5 Cd 0.5 S composite photocatalyst.
[0055] Embodiment 3
[0056] A CeO2 / Zn 0.5 Cd 0.5 The preparation method of S composite photocatalyst comprises the following steps:
[0057] S1. Preparation of CeO2 nanosheets:
[0058] S11. Dissolve 2.78 g of cerium nitrate hexahydrate and 1.50 g of ammonium bicarbonate in 100 ml of deionized water by stirring.
[0059] S12, the two solutions prepared in S11 were quickly mixed and continuously magnetically stirred for 30 minutes, and allowed to stand at 303 K for 24 hours. Centrifuged, washed, and dried at 353 K for 12 hours. Calcinated at 773 K for 4 hours to obtain CeO2 nanosheets.
[0060] S2. Preparation of CeO2 nanosheet suspension: Add 0.128 g of CeO2 nanosheet obtained in step S12 into 50 ml of deionized water and disperse by ultrasonic for 30 min.
[0061] S3. Prepare a mixed solution of cadmium acetate and zinc acetate: add 3 mmol of cadmium acetate dihydrate and 3 mmol of zinc acetate dihydrate into 40 ml of deionized water, stir to completely dissolve them, and obtain a homogeneous solution of cadmium acetate and zinc acetate.
[0062] S4. Prepare a sodium sulfide solution: add 6 mmol of sodium sulfide nonahydrate to 40 ml of deionized water, stir to completely dissolve it, and obtain a sodium sulfide solution.
[0063] S5, drip the mixed solution of cadmium acetate and zinc acetate obtained in S3 into the CeO2 nanosheet suspension obtained in S2 and stir for 1 hour, then slowly drip the sodium sulfide solution obtained in S4 and ultrasonicate for 30 minutes, then stir for 12 hours, the reaction product is centrifuged and washed with deionized water and ethanol, and freeze-dried to obtain 15% CeO2 / Zn 0.5 Cd 0.5 S composite photocatalyst.
[0064] Embodiment 4
[0065] A CeO2 / Zn 0.5 Cd 0.5 The preparation method of S composite photocatalyst comprises the following steps:
[0066] S1. Preparation of CeO2 nanosheets:
[0067] S11. Dissolve 2.78 g of cerium nitrate hexahydrate and 1.50 g of ammonium bicarbonate in 100 ml of deionized water by stirring.
[0068] S12, the two solutions prepared in S11 were quickly mixed and continuously magnetically stirred for 30 minutes, and allowed to stand at 303 K for 24 hours. Centrifuged, washed, and dried at 353 K for 12 hours. Calcinated at 773 K for 4 hours to obtain CeO2 nanosheets.
[0069] S2. Preparation of CeO2 nanosheet suspension: Add 0.182 g of CeO2 nanosheet obtained in step S12 into 50 ml of deionized water and disperse by ultrasonic for 30 min.
[0070] S3. Prepare a mixed solution of cadmium acetate and zinc acetate: add 3 mmol of cadmium acetate dihydrate and 3 mmol of zinc acetate dihydrate into 40 ml of deionized water, stir to completely dissolve them, and obtain a homogeneous solution of cadmium acetate and zinc acetate.
[0071] S4. Prepare a sodium sulfide solution: add 6 mmol of sodium sulfide nonahydrate to 40 ml of deionized water, stir to completely dissolve it, and obtain a sodium sulfide solution.
[0072] S5, drip the mixed solution of cadmium acetate and zinc acetate obtained in S3 into the CeO2 nanosheet suspension obtained in S2 and stir for 1 hour, then slowly drip the sodium sulfide solution obtained in S4 and ultrasonicate for 30 minutes, then stir for 12 hours, the reaction product is centrifuged and washed with deionized water and ethanol, and freeze-dried to obtain 20% CeO2 / Zn 0.5 Cd 0.5 S composite photocatalyst.
[0073] Experimental Testing
[0074] The CeO2 / Zn prepared in Examples 1 to 4 0.5 Cd 0.5 S composite photocatalyst as well as pure CeO2 photocatalyst and pure Zn 0.5 Cd 0.5 Structural analysis of the photocatalyst.
[0075] like Figure 1 The X-ray diffraction patterns (XRD) of different photocatalysts are shown in Figure . Figure 1 It can be seen that for CeO2, all peaks are consistent with the fluorite structure CeO2 (JCPDS No.43-1002). 0.5 Cd 0.5 S, the three diffraction peaks at 26.4°, 43.7° and 52.2° correspond to the (100), (110) and (200) crystal planes, respectively. The strong diffraction peaks of CeO2 indicate its high crystallinity, while Zn 0.5 Cd 0.5 The broad diffraction peak of S is the characteristic of quantum dots. 0.5 Cd 0.5 The XRD patterns of the S composite photocatalyst showed that the 0.5 Cd 0.5 The diffraction peak of S is also found, and with the increase of CeO2 content in the composite photocatalyst, the intensity of the diffraction peak gradually becomes stronger. In addition, no impurity peak is found, indicating that CeO2 / Zn 0.5 Cd 0.5 S composite photocatalyst.
[0076] The CeO2 / Zn prepared in Example 2 0.5 Cd 0.5 S composite photocatalyst, pure CeO2 photocatalyst and pure Zn 0.5 Cd 0.5 Structural analysis of the photocatalyst.
[0077] like Figure 2 Shown are scanning electron microscope (SEM) images of different photocatalysts. Figure 2(a) shows the morphology of pure CeO2 photocatalyst. CeO2 is composed of nanosheets, which are several microns in size and have a smooth and clean surface. Figure 2 (b) shows pure Zn 0.5 Cd 0.5 S photocatalysts are nanoparticles and tend to agglomerate. Figure 2 (c) and Figure 2 (d) shows that when Zn 0.5 Cd 0.5 After S is combined with CeO2, Zn 0.5 Cd 0.5 S nanoparticles are evenly distributed on the surface of CeO2 nanosheets, which greatly alleviates the 0.5 Cd 0.5 This 2D / 0D structure is beneficial to the separation and migration of photogenerated carriers and improves the photocatalytic hydrogen production activity.
[0078] The CeO2 / Zn prepared in Example 2 0.5 Cd 0.5 Structural analysis of the composite photocatalyst.
[0079] like Figure 3 As shown in Figure 2, the energy dispersive spectroscopy (EDS) element mapping clearly shows that Ce, O, Zn, Cd and S elements are uniformly distributed in the CeO2 / Zn 0.5 Cd 0.5 S composite photocatalyst, indicating that 2D / 0D CeO2 / Zn 0.5 Cd 0.5 Successful construction of S heterojunction.
[0080] like Figure 4 (a) shows a transmission electron microscope (TEM) image of Zn 0.5 Cd 0.5 The S nanoparticles are evenly distributed on the surface of CeO2 nanosheets, which is consistent with the results of SEM observations. Figure 4 (b) shows a high-resolution transmission electron microscopy (HRTEM) image, which shows that the lattice fringe spacing is 0.352 nm and 0.321 nm, corresponding to Zn 0.5 Cd 0.5 The (100) crystal plane of S and the (111) crystal plane of CeO2.
[0081] The CeO2 / Zn prepared in Examples 1 to 4 0.5 Cd 0.5 S composite photocatalyst, pure CeO2 photocatalyst and pure Zn 0.5 Cd 0.5 The application of S photocatalyst in photocatalytic water decomposition to produce hydrogen was tested for photocatalytic performance verification.
[0082] Through the photocatalytic decomposition of water to produce hydrogen, the CeO2, Zn 0.5 Cd 0.5 S and different ratios of CeO2 / Zn 0.5 Cd 0.5 Photocatalytic performance of S composite photocatalyst. Photocatalytic water splitting reaction to produce hydrogen is carried out in a photocatalytic water splitting system.
[0083] 20 mg of photocatalyst was dispersed in 100 ml of water containing chloroplatinic acid, 0.35 M Na2S and 0.25 M Na2SO3 were used as hole scavengers, the reaction temperature was maintained at around 6°C using a circulating water cooling system, a 300 W xenon lamp was used as a simulated solar light source, and the H2 production was determined by an online gas chromatograph.
[0084] like Figure 5 As shown in (a), they are 20% CeO2 / Zn 0.5 Cd 0.5 S composite photocatalyst, 15% CeO2 / Zn 0.5 Cd 0.5 S composite photocatalyst, 10% CeO2 / Zn 0.5 Cd 0.5 S composite photocatalyst, 5% CeO2 / Zn 0.5 Cd 0.5 S composite photocatalyst, pure CeO2 photocatalyst and pure Zn 0.5 Cd 0.5 The hydrogen production of S photocatalysts is similar to that of CeO2 and Zn 0.5 Cd 0.5 Compared with S, different ratios of CeO2 / Zn 0.5 Cd 0.5 The hydrogen production of S composite photocatalysts was significantly improved, showing a significantly enhanced photocatalytic hydrogen production activity. Figure 5 As shown in (b), they are 20% CeO2 / Zn 0.5 Cd 0.5 S composite photocatalyst, 15% CeO2 / Zn 0.5 Cd 0.5 S composite photocatalyst, 10% CeO2 / Zn 0.5 Cd 0.5 S composite photocatalyst, 5% CeO2 / Zn 0.5 Cd 0.5 S composite photocatalyst, pure CeO2 photocatalyst and pure Zn 0.5 Cd 0.5 Hydrogen production rate of S photocatalyst, 10% CeO2 / Zn 0.5 C d 0.5The S composite photocatalyst has the highest hydrogen production rate of 27.788 mmol·g -1 ·h -1 , about pure CeO2 and pure Zn 0.5 Cd 0.5 335 times and 2.19 times of S.
[0085] Therefore, the present invention adopts the above-mentioned CeO2 / Zn with 2D / 0D structure. 0.5 Cd 0.5 S composite photocatalyst and preparation method and application thereof, simple operation, low cost, 0D Zn 0.5 Cd 0.5 S nanoparticles are evenly distributed on the surface of 2D CeO2 nanosheets. 0.5 Cd 0.5 CeO2 / Zn is formed between S and CeO2 0.5 Cd 0.5 S heterojunction will greatly promote the separation and migration of photogenerated carriers.
[0086] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A CeO2 / Zn with 2D / 0D structure 0.5 Cd 0.5 The method for preparing S composite photocatalyst is characterized in that: The following steps are involved: S1, preparing CeO2 nanosheets; S2, preparing CeO2 nanosheet suspension; S3, preparing a mixed solution of cadmium acetate and zinc acetate; S4, preparing sodium sulfide solution; S5, according to a certain ratio, the mixed solution of cadmium acetate and zinc acetate obtained in S3 is dripped into the CeO2 nanosheet suspension obtained in S2 for stirring, and then the sodium sulfide solution obtained in S4 is slowly dripped into and stirred after ultrasonic treatment, and the CeO2 / Zn nanosheet suspension is obtained after centrifugation, washing and freeze drying. 0.5 Cd 0.5 S composite photocatalyst.
2. The CeO2 / Zn with 2D / 0D structure according to claim 1 0.5 Cd 0.5 The method for preparing S composite photocatalyst is characterized in that: S1 includes the following steps: S11, dissolving cerium nitrate hexahydrate and ammonium bicarbonate in deionized water respectively to obtain a cerium nitrate hexahydrate solution and an ammonium bicarbonate solution; S12. Add the cerium nitrate hexahydrate solution obtained in S11 to the ammonium bicarbonate solution obtained in S11, perform magnetic stirring, then let stand, centrifuge, and wash, collect the washed product, dry it, and then calcine it to obtain CeO2 nanosheets.
3. The CeO2 / Zn with 2D / 0D structure according to claim 2 0.5 Cd 0.5 The method for preparing S composite photocatalyst is characterized in that: In S11, the molar ratio of the cerium nitrate hexahydrate in the cerium nitrate hexahydrate solution to the ammonium bicarbonate in the ammonium bicarbonate solution is 1:1-4.
4. The CeO2 / Zn with 2D / 0D structure according to claim 2 0.5 Cd 0.5 The method for preparing S composite photocatalyst is characterized in that: In S12, the standing temperature is 293-313K and the time is 12-36h, the drying temperature is 70-110°C and the time is 8-15h, and the calcination temperature is 673-873K and the time is 2-8h.
5. The CeO2 / Zn with 2D / 0D structure according to claim 1 0.5 Cd 0.5 The method for preparing S composite photocatalyst is characterized in that: S2 is specifically: The CeO2 nanosheets obtained in S1 were added into deionized water, followed by ultrasonic dispersion treatment to obtain a CeO2 nanosheet suspension.
6. The CeO2 / Zn with 2D / 0D structure according to claim 1 0.5 Cd 0.5 The method for preparing S composite photocatalyst is characterized in that: In S3, the mixed solution of cadmium acetate and zinc acetate is cadmium acetate dihydrate: zinc acetate dihydrate: deionized water = 3mmol: 3mmol: 40ml.
7. The CeO2 / Zn with 2D / 0D structure according to claim 1 0.5 Cd 0.5 The method for preparing S composite photocatalyst is characterized in that: In S4, the sodium sulfide solution is sodium sulfide nonahydrate: deionized water = 3mmol: 20ml.
8. The CeO2 / Zn with 2D / 0D structure according to claim 1 0.5 Cd 0.5 The method for preparing S composite photocatalyst is characterized in that: In S5, the ultrasonic time of the post-ultrasonic stirring treatment is 20 to 40 minutes, and the stirring time is 8 to 24 hours.
9. A CeO2 / Zn with a 2D / 0D structure according to any one of claims 1 to 8 0.5 Cd 0.5 CeO2 / Zn S composite photocatalyst prepared by the preparation method 0.5 Cd 0.5 S composite photocatalyst, characterized in that The CeO2 / Zn 0.5 Cd 0.5 CeO2 and Zn in S composite photocatalyst 0.5 Cd 0.5 The mass ratio of S is 5-20:80-95.
10. A CeO2 / Zn with 2D / 0D structure as claimed in claim 9 0.5 Cd 0.5 Application of S composite photocatalyst in photocatalytic water decomposition to produce hydrogen.
Citation Information
Patent Citations
Preparation of a triptycene polymer NTP / zinc cadmium sulfide Cd0.5Zn0.5S composite photocatalyst
CN107876094A
Preparation method of tubular C3N4 / Cd0.5Zn0.5S composite photocatalyst
CN108855186A
CdZnS superfine nanoparticle loaded In2O3 fusiform nanorod composite material, and preparation method and application thereof
CN113385193A
Preparation method of ZnCdS / CeO2 composite photocatalytic material
CN118788361A
Cited By
Preparation method of composite nanoparticle photocatalyst
CN119926471A